Oral cavity: a horbor for metastasis - Srinivas, Naveen; Kotturu, Mohammed Fazil; Ramdurg, Praveenkumar; Rudrakshi , Anusha B. (International Journal Of Community Medicine And Public Health, 2024)
The early recognition and appropriate diagnosis of lesions or growths which do not appear to have probable aetiology is of utmost importance. In such cases metastatic lesion or secondary tumours should be considered in differential diagnosis. Metastasis from distinct organs, outside the head and neck region, accounts for about 1% of all malignancies of the oral cavity. A comprehensive approach to history-taking, clinical examination, and diagnostic evaluation is necessary when suspecting metastatic disease in the oral cavity. The most common primary sites are lung carcinoma in males and breast carcinoma in females, followed by renal cell carcinoma. It presents with clear cells and exhibit a tendency for hematogenous distant metastasis to various sites including the oral mucosal tissue. Renal cell carcinoma metastasis to the oral cavity is relatively rare, but it highlights the significance of thorough examination and consideration of metastatic disease in patients presenting with oral lesions, particularly those with a history of cancer. Here, we present a case of metastasis of renal cell carcinoma to oral cavity of a 65-year-old Male patient, which represented the first sign of disease.